SERVICES FOR PEOPLE WITH INTELLECTUAL DISABILITIES IN THE REPUBLIC OF MACEDONIA: VISION AND REALITY - Дамовски, Андон (Ревија за социјална политика/Journal of Social Policy, 2015)
The system of social protection of disabled people in the country toits independence generally was conducted by a medical model anddeveloped a system of institutional care. The reforms in the socialprotection system in the country (after establishing independence),develops and promotes the social protection of disabled people in theirplace of residence. The process of reforms in the field of social protectionwas developed in 2003 and the adoption of certain measures and the socialprotection policies are established in 2004 as a result of legislativeinitiatives.The new legislative initiatives and regulations created radicalchanges in the field of social sector by introducing new solutions. Socialreforms are based on three new principles of social protection (decentralization, social inclusion and social protection plural), in order tostrengthen and adjust the Macedonian system to European andinternational standards.Approaching european and international conceptions Ministry ofLabor and Social Policy, in its policies and strategies embarked on aprocess of transformation of public services, social protection of peoplewith intellectual disabilities through the processes of decentralization,disinstitutionalisation, privatization and implementation of joint projectsNGOs working in the field of social protection.In this paper will be analyzed the active local policies for peoplewith intellectual disabilities, as well as the capabilities and capacity oflocal government to open these services to people in the community,taking into account the above mentioned principles in social care.
Keywords: social services; social welfare; social policy; people with intellectual disabilities